1996
DOI: 10.1002/(sici)1097-0231(19960715)10:9<1027::aid-rcm634>3.3.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of Sialic Acids in N-linked Oligosaccharides and Gangliosides for Analysis by Positive Ion Matrix‐assisted Laser Desorption/Ionization Mass Spectrometry

Abstract: Matrix-assisted laser desorption/ionization (MALDI) mass spectrometry of oligosaccharides and gangliosides normally causes loss of sialic acid, particularly when alpha-cyano-4-hydroxycinnamic acid is used as the matrix. In addition, the potential signal is split because both positive and, to a greater extent, negative ions are formed while signals are frequently complicated as the result of partial alkali-salt formation. In order to stabilize the sialic acid moieties under MALDI conditions and to divert all of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
179
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 108 publications
(185 citation statements)
references
References 0 publications
5
179
1
Order By: Relevance
“…Neutral glycans yield intense signals in the positive ion mode corresponding to sodium-cationized molecular species [ 23 . Permethylation of glycans using the method described by Ciucanu and Kerek also stabilizes the sialic acid residues 24 .…”
Section: Release Of Glycansmentioning
confidence: 99%
“…Neutral glycans yield intense signals in the positive ion mode corresponding to sodium-cationized molecular species [ 23 . Permethylation of glycans using the method described by Ciucanu and Kerek also stabilizes the sialic acid residues 24 .…”
Section: Release Of Glycansmentioning
confidence: 99%
“…Several mass spectrometric approaches for analysis of glycan structures have been reported. [11][12][13][14][15][16][17]34,35 We analyzed N-glycans of these glycoproteins using MALDI-TOFMS in combination with exoglycosidase digestion. The results indicated that increases in α1-3 fucosylated, poly-fucosylated, and highbranched N-glycans occurred not only on transferrin but also on α1-antitrypsin, α2-HS-glycoprotein, and β2-glycoprotein.…”
Section: Discussionmentioning
confidence: 99%
“…Sialylated glycans from bovine fetuin and thyroglobulin appeared to lose much less of their sialic acid than when examined with the MALDI-TOF system; spectra were compared with those of stable permethylated samples (spectra not shown). However, even if desialylation is a problem, previous work has shown that sialic acid loss can be prevented by derivatization of the carboxy group of the sialic acids by methyl ester [33,34] or amide formation [35,61] or by selective formation of lactones from α2→3-linked sialic acids [34] with retention of the free hydroxyl groups that are necessary for production of the informative negative ion CID spectra.…”
Section: Positive Ionmentioning
confidence: 98%
“…The spectra of monosialylated glycans, in particular, retain many of the diagnostic ions (data not shown but see reference [64]). However, these glycans can be neutralized by derivatization [33,61], as mentioned above and, in some cases, the derivatization reaction can be exploited to provide linkage information for the sialic acids [34].…”
Section: Negative Ionmentioning
confidence: 99%
See 1 more Smart Citation